2016
DOI: 10.1371/journal.pone.0166943
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Motor Vehicle Collisions in Patients with Primary Open-Angle Glaucoma: A Multicenter Prospective Cohort Study

Abstract: PurposeTo identify the incidence rate of motor vehicle collisions (MVCs) in patients with no ocular pathology other than primary open-angle glaucoma (POAG) and determine the putative risk factors for MVCs in this group of patients.MethodsWe designed a prospective cohort study across three centers utilizing a consecutive sampling method to identify all patients with POAG between the ages of 40 and 80 years old. Patients with glaucoma were consecutively screened for eligibility. All study participants answered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
9
0
7
Order By: Relevance
“…Glaucoma is characterized by progressive optic neuropathy that could lead to visual function damage including VF defects and VA decrease [18]. Ophthalmologists paid close attention to these objective visual function indices in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is characterized by progressive optic neuropathy that could lead to visual function damage including VF defects and VA decrease [18]. Ophthalmologists paid close attention to these objective visual function indices in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This study consisted of a baseline cross-sectional study and a 3-year follow-up prospective cohort study. Descriptive research design, baseline evaluation of subjects with glaucoma, diagnostic criteria for POAG, and exclusion criteria were shown in our previous paper [ 11 , 12 ]. This is a sub-analysis of our two previous reports.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a prospective, multicenter study showed that the visual acuity of the worst eye is a significant risk factor for MVCs in patients with primary open-angle glaucoma (34) . Conversely, Gracitelli and colleagues found in a prospective study that the visual acuities of both best and worst eye were not predictive factors of MVCs (35) .…”
Section: Visual Acuity and Ability To Drivementioning
confidence: 99%